Disruption of Notch signaling by KGF induces a developmental pause in thymocytes - Teng, Ruifeng; Flomerfelt, Francis A.; Xue, Ping; Chandroth, Anjali; Noguchi, Constance Tom; Svoronos, Nikolaos; Gress, Ronald E.; Taylor, Naomi (Frontiers in Immunology, 2025)
Keratinocyte growth factor (KGF) has been proposed as a therapeutic adjuvant to enhance T cell immune reconstitution, particularly following stem cell transplantation. Here, we demonstrate that the long-term KGF-induced increase in thymic cellularity and thymocyte differentiation is preceded by a transient developmental block prior to the β-selection checkpoint, observed as early as day 2 following KGF treatment. This early block is characterized by an increased expansion of uncommitted thymocytes and is driven by KGF-induced alterations in both cortical and medullary thymic epithelial cells (TECs). KGF suppresses Wnt/β-catenin signaling by downregulating distinct Wnt ligands in cTECs and mTECs, leading to reduced expression of FOXN1, a master regulator of TEC differentiation. Consequently, expression of Foxn1-dependent genes, including Dll4, a key Notch ligand required for early thymocyte development, is diminished. These findings reveal a novel mechanism of KGF action: an initial disruption of TEC-mediated signaling that transiently impairs early thymocyte differentiation, followed by enhanced proliferation and long-term thymic recovery.